An introduction to bond markets - Choudhry, Moorad. (Wiley, 2010)
"The bond markets are a vital part of the world economy. The fourth edition of Professor Moorad Choudhry's benchmark reference text An Introduction to Bond Markets brings readers up to date with latest developments and market practice, including the impact of the financial crisis and issues of relevance for investors. This book offers a detailed yet accessible look at bond instruments, and is aimed specifically at newcomers to the market or those unfamiliar with modern fixed income products. The author capitalises on his wealth of experience in the fixed income markets to present this concise yet in-depth coverage of bonds and associated derivatives.Topics covered include:Bond pricing and yieldDuration and convexityEurobonds and convertible bondsStructured finance securitiesInterest-rate derivativesCredit derivativesRelative value tradingRelated topics such as the money markets and principles of risk management are also introduced as necessary background for students and practitioners. The book is essential reading for all those who require an introduction to the financial markets"--